EVALUATION OF FOREST FIRES IN PARANÁ IN 2018 AND 2019 - Zamproni, Kendra; Ferreira, Heitor Renan; Batista, Antonio Carlos (Floresta, 2021)
Forest fires represent significant environmental, economic, and social damage in many countries. Historical knowledge of their characteristics aids in making preventive decisions, as well as fighting forest fires. However, the general data of fires in Paraná are outdated. The objective of this study was to evaluate the forest fires in the state of Paraná in 2018 and 2019, surveying the following information: municipality and region affected; month and day of occurrence; and vegetation type. To this end, data obtained from the Paraná Fire Department through the SysBMNew-CCB platform were analyzed. The fire density by region was verified and compared through cluster analysis. Compared to the previous year, 2019 showed a 42.25% increase in the number of fires. In both years, most forest fires occurred in the North-central region, followed by the Metropolitan Region of Curitiba. The municipality of Curitiba recorded the highest number of fires in both years. According to the Fire Department classification, the vegetation type most affected by the fires was vacant lots. From the data obtained, we verified the need for environmental education measures aimed at the prevention of fires in vacant lots. Further research is recommended so that a profile of forest fires can be traced in the state and thus base prevention and control measures.